Enhancing Reading Comprehension Through Extensive Reading - Fergina, Ana; Ghazy, Ahmad; Prancisca, Stella; Aminah, Syarifah; Ananda, Elsa (Journal of English Education Program, 2024)
Numerous studies support extensive reading as beneficial for second language learners, enhancing vocabulary, grammar, writing, and overall English proficiency. However, there is still a small number of research on how this technique influences students' ability to answer reading comprehension questions. Extensive reading and reading comprehension have quite different reading goals. Extensive reading aims to make readers enjoy reading material and can choose reading materials according to the reader's level. Meanwhile, reading comprehension emphasizes students' level of understanding about the details of reading material. This research aims to look at the effect of extensive reading strategies on students' ability to answer reading comprehension questions. The method used in this research is experimental by using "One Group Pretest-Posttest Design". This design requires to conduct pre-test before implementing the treatment then followed by conducting post-test once it"™s done. The results of this study indicated that the extensive reading strategy applied to class A of Islamic Economics Study Program for 1 semester can significantly improve the quality of students' understanding in answering Reading Comprehension questions. This improvement can be seen from the results obtained in the pretest and post-test which have been conducted before and after treatment (Extensive Reading). By conducting the extensive reading it can bolster students' academic scores by cultivating a deep-seated comprehension, vocabulary breadth, and critical thinking skills. Through consistent exposure to diverse texts, students enhance their overall literacy, fostering a solid foundation for improving academic performance